The Impact of Accounting Systems, Financial Report Accessibility, and Internal Control on Regional Financial Accountability: A Systematic Literature Review - Sufardi; Sirnan (JEKAMI Journal of Accounting, 2025)
This research aims to analyze the impact of accounting systems, financial report accessibility, and internal control on regional financial accountability through a systematic literature review (SLR) approach. Regional financial accountability is an important aspect of good governance, which reflects transparency, compliance with regulations, and the effectiveness of regional financial management. The research results show that implementing an accounting system that is in accordance with Government Accounting Standards (SAP) can increase the accuracy and transparency of regional financial reports. In addition, good accessibility of financial reports contributes to increasing public participation in regional financial supervision. Strong internal control is also a key factor in preventing deviations and increasing budget management efficiency. However, challenges in implementing modern accounting systems, limited accessibility of financial reports, and weaknesses in internal control are still obstacles in increasing regional financial accountability. Therefore, efforts are needed to improve human resource competence, strengthen regulations related to transparency, and optimize the use of technology in government accounting systems.